Dosage calculations for medical careers - Haddix, Kathryn A. (Glencoe/McGraw-Hill, 2002)
Dosage Calculations for Medical Careers teaches the skills and techniques medical assistants, licensed practical nurses, pharmacy technicians, and paramedics need to calculate the amount of medication they should administer to patients. Students learn to calculate dosages based on ratio proportions, fraction proportions, the formula method, and dimensional analysis.